1959
DOI: 10.5962/bhl.title.6423
|View full text |Cite
|
Sign up to set email alerts
|

The mast cells

Abstract: 'coarse granulocyte' in echinoderms is first recognizable as a connective tissue cell with clear cytoplasm, and thus corresponds to the 'hyaline cell' of Kollmann (1908). Under conditions of good feeding the cell develops bulky refractile spherules which stain with basic dyes. The spherules then progressively become yellow and shrunken; finally often red and acidophilic. Thus the intermediate coarse granulocyte in invertebrates, the cell with colourless, basophilic spherules, bears the most obvious resemblance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(9 citation statements)
references
References 139 publications
(192 reference statements)
1
8
0
Order By: Relevance
“…Therefore, there does not appear to be a histamine-mediated component in the decrease in MAP caused by N-type calcium channel blockade in the conscious rabbit. This ®nding is consistent with the sparse distribution of tissue mast cells surrounding the microcirculation in the rabbit compared with a dense mast cell population in rats and mice (Riley, 1959). Similarly, but in contrast to the ®ndings in the conscious rat of Bowersox et al (1992), H 1 , H 2 and H 3 receptor antagonism did not signi®cantly aect the pIC 50 for MVIIA in the rat right atrial assay.…”
Section: Conscious Rabbit Experimentssupporting
confidence: 70%
“…Therefore, there does not appear to be a histamine-mediated component in the decrease in MAP caused by N-type calcium channel blockade in the conscious rabbit. This ®nding is consistent with the sparse distribution of tissue mast cells surrounding the microcirculation in the rabbit compared with a dense mast cell population in rats and mice (Riley, 1959). Similarly, but in contrast to the ®ndings in the conscious rat of Bowersox et al (1992), H 1 , H 2 and H 3 receptor antagonism did not signi®cantly aect the pIC 50 for MVIIA in the rat right atrial assay.…”
Section: Conscious Rabbit Experimentssupporting
confidence: 70%
“…The distribution of mast cells in the rat skin is not uniform; they are more numerous in the subcutaneous tissue than in the dermis and tend to concentrate perivascularly along the panniculus carnosus, as was found by Riley (1959). The changes in mast cell number following transplantation is illustrated in Figure 4.…”
Section: Histology and Mast Cellpopulation Ofgraftsmentioning
confidence: 81%
“…[1] Studies on mast cells in normal and various pathologic conditions have shown them to be complex, well-engineered, multifunctional cell playing a central role in acquired and innate immunity.…”
Section: Introductionmentioning
confidence: 99%